New phenomena in the everyday life of Kazakhs of Zhetysu (ІІ part of ХІХ- beg. ХХ) (Journal of history, 2017)
The article examines the changes in the everyday life of the Kazakhs of the Zhetisu that occurred during the pre-revolutionary period. Based on archival materials, historical-literary and historical-ethnographic studies, the influence of political and economic factors on changes in family and kinship relations of the Kazakhs of the Zhetisu oblast is analyzed.For a comprehensive description of the difficulties that have fallen on the everyday life of the Kazakhs was usedinformation from the works of "Zar zaman"Akynswho lived in the ХІХ-ХХ centuries ("Epochs of Sorrow") and testimonies from the memories of individual people recorded in expeditions.The article presents the results of the colonial impact on the life of the Kazakhs of the Zhetisu, as well as new and incomprehensible phenomena that have changed the traditional mentality of everyday life of the Kazakhs.